Influence of Climate and Land Use Change on Spatially Resolved Volatilization of Persistent Organic Pollutants (POPs) from Background Soils - Komprda, Jiří; Komprdová, Klára; Sáňka, Milan; Možný, Martin; Nizzetto, Luca (Environmental science & technology, 2013)
The subject of this study is the assessment of the influence of climate and land use change on the potential re-emission of organochlorine pesticides (OCPs) from background and agricultural soils. A deterministic spatially and temporally explicit model of the air–surface exchange was created, fed with distributed data of soil and atmospheric concentrations from real measurements, and run under various scenarios of temperature and land use change for a case study area representative of central European conditions. To describe land use influence, some important features were implemented including effect of plowing, influence of land cover, temperature of soil, and seasonal changes of air layer stability. Results show that volatilization of pesticides from soil largely exceeded dry gas deposition in most of the area. Agricultural soils accounted for more than 90% of the total re-emissions both because of the generally higher soil fugacities (higher loads of chemicals and relatively low organic carbon content), but also due to physical characteristics and land management practices enhancing the dynamics of the exchange. An increase of 1 °C in air temperature produced an increase of 8% in the averaged total volatilization flux, however this effect can be neutralized by a change of land use of 10% of the arable lands to grassland or forest, which is consistent with projected land use change in Europe. This suggests that future assessment of climate impact on POP fate and distribution should take into consideration land use aspects.